Molecular Markers of MDR of Chemotherapy for HSCC: Proteomic Screening With High-Throughput Liquid Chromatography-Tandem Mass Spectrometry - Shen, Bin; Dong, Xuelin; Yuan, Bo; Zhang, Zhijun (Frontiers in Oncology, 2021)
Background: Hypopharyngeal squamous cell cancer is a head and neck tumor with a poor prognosis. Chemotherapy lacks effectiveness because of multidrug resistance, which has increased toxic side effects. Thus, there is an urgent need to identify the molecular markers of MDR of chemotherapy for HSCC. Methods: Fifty clinical samples of HSCC were derived from patients including 12 sensitive or resistant to chemotherapy drugs. Proteomic screening was performed using liquid chromatography-tandem mass spectrometry, which was based on data-independent acquisition. Molecular markers of MDR of chemotherapy in patients with HSCC were identified with clinical data and validated with ELISA. Results: A total of 673 differentially expressed proteins were identified in HSCC samples, where 172 were upregulated and 501 were downregulated. A total of 183 differentially expressed proteins including 102 upregulated and 81 downregulated proteins, were identified by comparing cancer sensitive to chemotherapy with cancer resistant to chemotherapy. Clinical HSCC samples had significantly higher expression of FADD and significantly lower expression of RIPK1. Expressions of FADD and RIPK1 proteins were significantly lower in the chemotherapy-sensitive group. These expression differences were not correlated with clinical data. RIPK1 and FADD are involved in necroptosis and the signaling pathway of PRRs. Using ELISA, the low expression of RIPK1 and FADD was found in the patients sensitive to chemotherapy. Conclusion: LC-MS proteomics is an effective method to identify the molecular markers of HSCC. FADD and RIPK1 can act as molecular markers of MDR of chemotherapy in patients with HSCC and may function through necroptosis and the PRR signaling pathway.